2008
DOI: 10.1016/j.jmb.2008.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Free-Energy Landscapes of the Wild Type and Mutants of the Aβ21–30 Peptide Are Determined by an Interplay between Intrapeptide Electrostatic and Hydrophobic Interactions

Abstract: The initial events in protein aggregation involve fluctuations that populate monomer conformations which lead to oligomerization and fibril assembly. The highly populated structures, driven by a balance between hydrophobic and electrostatic interactions in the protease-resistant wild type Aβ 21-30 -peptide and mutants E22Q (Dutch), D23N (Iowa), and K28N, are analyzed using molecular dynamics simulations. Intra-peptide electrostatic interactions were connected to calculated pK a values that compare well with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
84
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 56 publications
14
84
0
Order By: Relevance
“…With an aggregate of 1.7 μs of SMD simulations, we found that peptide bindings on hydrophobic (H) sides are significantly more stable than bindings on hydrophilic (P) sides, which is concordant with our previous findings that the hydrophobic interaction dominates the longitudinal growth of GAV-9 nanofilaments on mica (26). This significance of hydrophobic interactions (and lowering of the desolvation penalty) was also emphasized in the studies on charged amyloid peptides aggregation of Thirumalai and coworkers (30,31). The binding free energies are also comparable on the H edges for both the AP and P2 models (ΔG bind ≈ −32 kcal/mol).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…With an aggregate of 1.7 μs of SMD simulations, we found that peptide bindings on hydrophobic (H) sides are significantly more stable than bindings on hydrophilic (P) sides, which is concordant with our previous findings that the hydrophobic interaction dominates the longitudinal growth of GAV-9 nanofilaments on mica (26). This significance of hydrophobic interactions (and lowering of the desolvation penalty) was also emphasized in the studies on charged amyloid peptides aggregation of Thirumalai and coworkers (30,31). The binding free energies are also comparable on the H edges for both the AP and P2 models (ΔG bind ≈ −32 kcal/mol).…”
Section: Resultssupporting
confidence: 90%
“…The AP model stabilizes the binding by ∼12 kcal/mol for a single peptide, whereas the P2 model stabilizes binding by only ∼4 kcal/mol. This indicates that the ionic strength (i.e., ∼6 Å of Debye length) might not be enough to screen out electrostatic repulsion in the P2 model between shortdistanced (<5 Å) peptides along the transversal hydrophilic sides (linked by backbone hydrogen bonds), although for the relatively long-distanced (∼10 Å) peptides along the longitudinal direction (due to bulky side chains), the electrostatic repulsion is no longer a major force due to the longer distance and more effective screening; thus, both the AP and P2 models give similar binding affinities due to their comparable hydrophobic interactions (30,31). Our PMF results therefore further support that the AP model is thermodynamically more stable than the P2 model for the upper layers, which largely comes from the aid of a more supportive transversal lateral interaction in its antiparallel arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Much work on surface properties of protein molecules, and the evaluation of hydrophobicity by the hydrophobic fluorescence probe [7] or by thermodynamic approaches [8] has been reported. Conventionally, the summation of hydrophobicity of the constituent amino acids gave the hydrophobicity of the protein as a whole [9], which is not useful in explaining the hydrophobic interaction between proteins as shown in Fig.1.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the stable structures of proteins can be predicted as minima of the free-energy landscape, and it is possible to elucidate specific interactions that give rise to the stable structures [7,[22][23][24]. It is, in a sense, surprising that these two different concepts, one being a dynamical concept of force and the other being a statistical distribution, can be given by the same energy function.…”
mentioning
confidence: 99%
“…Its application can be found in the studies of, for example, large molecules, such as clusters [1,2] and proteins [3][4][5][6][7][8][9][10], diffusion in oxide networks [11], fullerene materials [12], formation process of gels and glasses [13], chemical and biological separation through micro-and nanofluidic systems [14], and epigenetics in developmental biology [15][16][17]. Two important roles of the energy landscape can be pointed out.…”
mentioning
confidence: 99%